Technology in action - Heath, Christian, 1952- (Learning in doing., 2000)
This book explores the way complex systems affect everyday work and interaction through video-based field studies looking at the introduction of basic information systems in general medical practice, news production, the control room of London Underground and computer aided design in architectural practice.